The Labeling of Good and Evil in “Descendants” - Alicia Nagaseta (Kata Kita: Journal of Language, Literature, and Teaching, 2018)
This paper aims to discuss the instilment of good and evil as well as their effects to the royal and villains’ children. I will use the theories of labeling, social identity, and self-concept to analyze the topic. Labeling theory is applied to analyze the ways the labels good and evil are formed through the parents’ past interaction with each other before they instilled it to their children. Social identity theory is used to analyze the ways the children construct their identities depending on the social group they live in. Finally, self-concept theory is applied in providing the ways that the labels good and evil shape the children’s perspective and behavior toward themselves. In the end, it can be concluded that the labeling of good and evil in Descendants could be passed down from parents to children.The labels, along with social groups and other people’s opinions could shape the children’s self-concept about themselves.